2021
DOI: 10.3390/ijms22063141
|View full text |Cite
|
Sign up to set email alerts
|

Mapping of Microglial Brain Region, Sex and Age Heterogeneity in Obesity

Abstract: The prevalence of obesity has increased rapidly in recent years and has put a huge burden on healthcare worldwide. Obesity is associated with an increased risk for many comorbidities, such as cardiovascular diseases, type 2 diabetes and hypertension. The hypothalamus is a key brain region involved in the regulation of food intake and energy expenditure. Research on experimental animals has shown neuronal loss, as well as microglial activation in the hypothalamus, due to dietary-induced obesity. Microglia, the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 112 publications
0
8
0
Order By: Relevance
“…Up until recently, rodent studies on metabolic disorders mainly focused on males and sex differences have been understudied, especially concerning microglia. However, emerging data are pointing to a strong heterogeneity of microglia between males and females [ 40 , 41 ]. A study by Dorfman et al, showed that a sex-specific CX3CR1 hypothalamic signaling is at the core of obesity progression, with female mice maintaining a level of resistance to DIO [ 42 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Up until recently, rodent studies on metabolic disorders mainly focused on males and sex differences have been understudied, especially concerning microglia. However, emerging data are pointing to a strong heterogeneity of microglia between males and females [ 40 , 41 ]. A study by Dorfman et al, showed that a sex-specific CX3CR1 hypothalamic signaling is at the core of obesity progression, with female mice maintaining a level of resistance to DIO [ 42 ].…”
Section: Discussionmentioning
confidence: 99%
“…In summary, the findings of this study highlight the importance of microglial insulin signaling in the CNS control of energy metabolism and the sex-dependent differences observed during the progression of obesity. Microglial cells seem to show a vast difference in their phenotype between males and females in an age-, region-, and disease-dependent manner [ 40 , 41 , 44 ]. Our findings provide further insight into the complex mechanisms that are operative in the brain for the control of energy metabolism in health and disease and highlight the importance of taking into account possible sex-dependent differences in these mechanisms.…”
Section: Discussionmentioning
confidence: 99%
“…HFD increases Iba-1 expression in the arcuate nucleus (ARC), paraventricular nucleus (PVN), and hippocampus. No specific microglial changes are observed in the cerebral cortex and striatum ( Thaler et al, 2012 ; Milanova et al, 2021 ). In the medio -basal hypothalamus (MBH), microgliosis is mediated by activating pathways such as NF-κB, favoring cell infiltration, increased food intake, and local inflammation ( Valdearcos et al, 2017 ).…”
Section: Chronic Obesity and Neuroinflammationmentioning
confidence: 97%
“…However, evidence has begun to emerge that systemic inflammation, either induced with peripheral LPS or the administration of one or more of the pro-inflammatory cytokines such as TNFα, IL1β, IL6, IL33, is involved in microglial priming ( Perry and Holmes, 2014 ; Li J. W. et al, 2018 ). Due to the heterogeneity of microglial density depending on the brain region, brain structures are differentially affected; the main affected brain regions are the hypothalamus, hippocampus, cerebral cortex, and striatum ( Milanova et al, 2021 ). Another example is the NLRP3 protein of the inflammasome in visceral adipose tissue, which directly affects IL1ß levels in the brain, activating microglia through the IL1R1 receptor and thus affecting memory in obese animals ( Guo et al, 2020 ).…”
Section: Chronic Obesity and Neuroinflammationmentioning
confidence: 99%
“…Another concern derives from the neurological alterations associated with diabetes that affect cognitive functions, but also sensory and motor control functions [ 7 ]. The neurological manifestations are due to functional and structural alterations, some of which present variable degrees of microglial activation [ 8 , 9 , 10 , 11 ]. For ethical reasons derived from the invasiveness of obtaining it, cerebrospinal fluid (CSF) has not been extensively studied in diabetic patients.…”
Section: Introductionmentioning
confidence: 99%